2003
DOI: 10.1128/aac.47.5.1736-1738.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Linezolid against Slowly Growing Nontuberculous Mycobacteria

Abstract: MICs of linezolid in broth microdilutions were tested against 341 slowly growing nontuberculous mycobacteria (NTM) belonging to 15 species. The proposed linezolid susceptibility MICs for all Mycobacterium marinum, Mycobacterium szulgai, Mycobacterium kansasii, Mycobacterium malmoense, and Mycobacterium xenopi isolates and for 90% of Mycobacterium gordonae and Mycobacterium triplex isolates were <8 g/ml. Linezolid has excellent therapeutic potential against most species of NTM.Treatment of infections due to slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 9 publications
4
40
0
Order By: Relevance
“…In the present study, linezolid demonstrated similar activities against most mycobacterial isolates in agreement with previous reports (5,6). However, the M. avium complex and M. abscessus required 32 mg/L to inhibit 90z of the isolates tested, indicating that treatment with linezolid against these two species is difficult.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In the present study, linezolid demonstrated similar activities against most mycobacterial isolates in agreement with previous reports (5,6). However, the M. avium complex and M. abscessus required 32 mg/L to inhibit 90z of the isolates tested, indicating that treatment with linezolid against these two species is difficult.…”
supporting
confidence: 79%
“…In the second-line drugs, the highest drug resistance rate was to PAS (91.5z), followed by ofloxacin (69.2z), while the lowest resistant rates were for amikacin and capreomycin. Linezolid showed excellent activity against M. kansasii, and M. fortuitum, with MIC ranges of 0.5-1 mg/L and 0.5-8 mg/L, respectively, which was in accordance with previous reports (5,6). Similarly, the in vitro activities of sy142 and sy144 against these two species were comparable to those of linezolid.…”
supporting
confidence: 78%
“…Linezolid has also been demonstrated to be a useful agent for the treatment of disseminated disease caused by M. chelonae, although the risk of toxicity requires the careful monitoring of long-term therapy (i.e., 3 to 6 months) (55). Approximately 94% of isolates of M. chelonae have linezolid MICs in the susceptible range (53,415). Because isolates vary in their susceptibilities to these oral agents, in vitro susceptibility testing to determine the optimal drug treatment is warranted (410,426).…”
Section: Disseminated Diseasementioning
confidence: 99%
“…Many documented SGM species demonstrate susceptibility to macrolides, and these agents are now a cornerstone of most SGM regimens (9). Linezolid demonstrates high oral drug availability and good in vitro susceptibility against a broad range of SGM, but it differs depending on the strain of nontuberculous Mycobacterium that is being treated (13,14). Finally, ciprofloxacin is relatively well tolerated with a low side effect profile and has a relatively broad coverage of the SGM group at achievable MICs (15).…”
Section: Paraffinicum Was Initially Isolated From a Soil Sample Inmentioning
confidence: 99%